FREQUENCY OF PREMENSTRUAL SYNDROME AND EFFEC- TIVENESS OF GROUP COUNSELING IN REDUCING THE SE- VERITY OF SYMPTOMS IN FEMALE STUDENTS - Shobeiri, Fatemeh; Ebrahimi, Reihaneh; Ezati Arasteh, Fahimeh; Nazari, Sasan; Nazari, Saman (Journal of Postgraduate Medical Institute, 2018)
Objectives: To determine the frequency of premenstrual syndrome and effec- tiveness of group counseling in reducing the severity of symptoms of premen- strual syndrome in female students of Hamadan University of Medical Sciences. Methodology: This quasi-experimental study was conducted on 80 female stu- dents with definite diagnosis of premenstrual syndrome (PMS) in the University of Medical Sciences, Hamadan, Iran, in 2014. They were allocated randomly into two groups (intervention and control), each group having 40 members. Three counseling sessions were performed in the intervention group. Assessment was performed before the intervention and then after one and two months' post-intervention). Questionnaire of provisional diagnosis of PMS and invento- ry of overall severity of symptoms of PMS were used. Analysis of the data was performed by SPSS/16, using chi-square and paired t-tests. P value < 0.05 was regarded as significant. Results: Frequency of PMS was 56% among the students. Both groups were similar at the beginning of the study as demonstrated by Kolmogorov-Smirnov test. Mean scores of PMS symptoms (including anxiety, depression, emotional, water retention and somatic changes) were decreased significantly in the inter- vention group (p <0.05). Conclusion: Premenstrual syndrome was found in higher frequency among university students. Group counseling was significantly effective in improving the symptoms of premenstrual syndrome.